PARTIAL ADJUSTMENT TO TARGET CAPITAL STRUCTURE OF PROPERTY, REAL ESTATE AND CONSTRUCTION FIRMS - Muhammad Prayoga, Eggy
During Joko Widodo reign from 2014-2019 Infrastructure is one of the sectors that is developed massively. The development of infrastructure is assigned to the State-Owned Enterprise (SOE) and private sector. Since the development of infrastructure sector is done massively, the construction firms who is assigned to take the project might have a disturbance in their capital structure due to the financing needs to finance the project. The managers need to put attention to the capital structure of the firm and manage it properly in order to achieve the firm goal which is maximizing the firm value. This study aims to analyze the determinants of capital structure, optimal capital structure and speed of adjustment of property, real estate and construction firms. The population of this study is all firms in property, real estate and construction sector listed in Indonesia Stock Exchange. This study used secondary data from firm annual report to be analyzed using unbalanced panel data regression with GMM estimator. This study used dynamic model of capital structure based on trade-off theory. The determinant of capital structure based on dynamic model is profitability, tangibility, size, liquidity and non-debt tax shield. Profitability, tangibility, size and liquidity have a negative relationship while non-debt tax shield have a positive relationship. Based on the regression result, property, real estate and construction firm do have an optimal capital structure target with speed of adjustment 78% per year. Based on the calculation, property, real estate and construction firms need approximately 3 years to close the gap between current capital structure and target capital structure.